"Defect-free" interlayer with a smooth surface and controlled pore-mouth size for thin and thermally stable Pd composite membranes. (12th January 2016) - Zheng, Lei; Li, Hui; Xu, Hengyong
Abstract: Thin and thermally stable Pd membrane can be successfully coated on "defect-free" alumina sol/γ-Al2 O3 interlayer with a controlled pore-mouth size of ca. 0.08 μm obtained by modified sol–gel method on macroporous α-Al2 O3 support. The "modified" bubble-point method and home-developed "modified" liquid-liquid displacement method were used to check the size and amount of defects (>3 μm), and characterize pore-mouth size distribution of interlayers, respectively. The modified sol–gel method shows superiority in smoothening out defects and bumps compared to conventional suspended particles sintering method as the incorporation of alumina sol–gel particles can significantly improve the adhesion and dispersal uniformity of γ-Al2 O3 particles. The synthesized Pd composite membranes of 4.5 μm thickness exhibit high hydrogen permeance and selectivity compared to similar studies. In addition, the good membrane stability was verified by the long-term operation under hydrogen permeation conditions. This can be mainly ascribed to the formation of defect-free and smooth interlayer which effectively suppress the shear stress between Pd layer and intermediate layer when enduring thermal cycles and hydrogen adsorption and desorption cycles. Highlights: Modified sol–gel method combined with innovative pore size characterization methods. "Defect-free" interlayer (<3 μm) with smooth surface and controlled pore-mouth size. Shear stress between Pd layer and interlayer was significantly suppressed. Thin and thermally stable Pd composite membranes were successfully achieved.